Clinical utility of RNA sequencing to resolve unusual GNE myopathy with a novel promoter deletion. Issue 1 (29th April 2019) - Chakravorty, Samya; Berger, Kiera; Arafat, Dalia; Nallamilli, Babi Ramesh Reddy; Subramanian, Hari Prasanna; Joseph, Soumya; Anderson, Mary E.; Campbell, Kevin P.; Glass, Jonathan; Gibson, Greg; Hegde, Madhuri
ABSTRACT: Introduction : UDP N‐acetylglucosamine2‐epimerase/N‐acetylmannosamine‐kinase ( GNE ) gene mutations can cause mostly autosomal‐recessive myopathy with juvenile‐onset known as hereditary inclusion‐body myopathy (HIBM). Methods : We describe a family of a patient showing an unusual HIBM with both vacuolar myopathy and myositis without quadriceps‐sparing, hindering diagnosis. We show how genetic testing with functional assays, clinical transcriptome sequencing (RNA‐seq) in particular, helped facilitate both the diagnosis and a better understanding of the genotype‐phenotype relationship. Results : We identified a novel 7.08 kb pathogenic deletion upstream of GNE using array comparative genomic hybridization (aCGH) and a common Val727Met variant. Using RNA‐seq, we found only monoallelic (Val727Met‐allele) expression, leading to 50% GNE reduction in muscle. Importantly, α‐dystroglycan is hypoglycosylated in the patient muscle, suggesting HIBM could be a "dystroglycanopathy." Conclusions : Our study shows the importance of considering aCGH for GNE‐myopathies, and the potential of RNA‐seq for faster, definitive molecular diagnosis of unusual myopathies. Muscle Nerve, 2019